Analysis of the Effect of Hydrogen Chloride Impurities on the Copper-Vapor Laser Performance; Laser Physics; Vol. 14, No. 7 - Boichenko A. M.; Evtushenko G. S. Gennady Sergeevich; Yakovlenko S. I.; Zhdaneev O. V. (2004, 2004)
A nonstationary kinetic model of the active medium of a copper-vapor laser ( = 510.6 and 578.2 nm) with hydrogen chloride impurities is constructed. A theoretical analysis of the existing concepts regarding the increase in the lasing parameters of a copper-vapor laser with hydrogen chloride impurities in the active medium is presented. It is demonstrated that the effect of hydrogen chloride at high repetition rates of the exci-tation pulses differs from the effect at low repetition rates. At low repetition rates, the main contribution to the increase in the laser energy is related to the increase in the concentration of copper atoms in the ground state in the active medium, whereas at high repetition rates (higher than 50 kHz) the main reason is the decrease in the prepulse electron concentration.